2009
DOI: 10.1126/science.1169512
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Superglass State in Solid 4 He

Abstract: Although solid helium-4 (4He) may be a supersolid, it also exhibits many phenomena unexpected in that context. We studied relaxation dynamics in the resonance frequency f(T) and dissipation D(T) of a torsional oscillator containing solid 4He. With the appearance of the "supersolid" state, the relaxation times within f(T) and D(T) began to increase rapidly together. More importantly, the relaxation processes in both D(T) and a component of f(T) exhibited a complex synchronized ultraslow evolution toward equilib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
169
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(203 citation statements)
references
References 35 publications
25
169
2
2
Order By: Relevance
“…On the other hand, we found that the thermal conductivity is insensitive to the amplitude of oscillations. As was noted earlier [25,26], the dependences of the TO resonant frequency on amplitude V look basically identical to the temperature dependences Fig. 5), our exponent γ ≈ 0.71 is substantially different.…”
Section: Torsion Oscillations Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, we found that the thermal conductivity is insensitive to the amplitude of oscillations. As was noted earlier [25,26], the dependences of the TO resonant frequency on amplitude V look basically identical to the temperature dependences Fig. 5), our exponent γ ≈ 0.71 is substantially different.…”
Section: Torsion Oscillations Resultssupporting
confidence: 86%
“…The logarithmic width of the cross-over, * * high low / T T is greater than unity and keeps increasing with increasing * T . Table 1 Driving a torsional oscillator at large amplitude is known to suppress the effect [10,25]; we confirm this. On the other hand, we found that the thermal conductivity is insensitive to the amplitude of oscillations.…”
Section: Torsion Oscillations Resultssupporting
confidence: 69%
“…Indeed, later numerical results point towards such a possibility. 22 Notably, recent experimental results 13 agree with an earlier suggested theory concerning such transient dynamics. 14 The presence of non-uniformity in 4 He is also suggested by a criterion comparing the change in dissipation vs. relative period shift in torsion oscillator.…”
Section: Introductionsupporting
confidence: 82%
“…12 Relaxational dynamics in torsional oscillators has also been reported by the Cornell group of Davis. 13 The torsional oscillator findings can arise from material characteristics alone. [14][15][16][17][18][19][20][21] In particular, the thermodynamics and transient dynamics of distributed processes in amorphous or general non-equilibrated solids can currently fit 9,14 observed results.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of these two theories is markedly different, suggesting the possibility of non-trivial emergent physics over the full range of parameters that tune between the classical and quantum limits. Although this formulation makes no explicit mention of particle statistics, such an extension is possible, enabling treatment of purported glass formation in systems with a finite superfluid fraction [7][8][9] .The fully microscopic QMCT allows for a detailed description of the dynamical phase diagram that separates an ergodic fluid region from an arrested glassy one as a function of both thermodynamic control variables and the parameters (for exampleh) that control the size of quantum fluctuations. To illustrate this, we carry out detailed QMCT calculations on a hard-sphere system as a function of the system's volume fraction φ and the dimensionless parameter Λ * , which is the ratio of the de Broglie thermal wavelength to the particle size and controls the scale of quantum behaviour.…”
mentioning
confidence: 99%